2004
DOI: 10.1002/icd.365
|View full text |Cite
|
Sign up to set email alerts
|

Co‐sleeping: Help or hindrance for young children's independence?

Abstract: This study investigated the relationship between sleep arrangements and claims regarding possible problems and benefits related to co-sleeping. Participants were 83 mothers of preschoolaged children. Data were collected through parent questionnaires. Early co-sleepers (who began co-sleeping in infancy), reactive co-sleepers (children who began co-sleeping at or after age one), and solitary sleepers were compared on the dimensions of maternal attitudes toward sleep arrangements; night wakings and bedtime strugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 44 publications
(80 reference statements)
10
79
1
1
Order By: Relevance
“…In addition, mothers provided information in Keller and Goldberg’s (2004) Sleep Practices Questionnaire (SPQ) about whether they thought they had adequate sleeping space for everyone in their household. That specific SPQ item was, “We have limited sleeping space”, to which mothers responded on a five-point scale (1 = “ Not at all , 5 = “ Definitely ”).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, mothers provided information in Keller and Goldberg’s (2004) Sleep Practices Questionnaire (SPQ) about whether they thought they had adequate sleeping space for everyone in their household. That specific SPQ item was, “We have limited sleeping space”, to which mothers responded on a five-point scale (1 = “ Not at all , 5 = “ Definitely ”).…”
Section: Methodsmentioning
confidence: 99%
“…The Sleep Practices Questionnaire (SPQ; Keller & Goldberg, 2004) was the primary source of information about infant sleep and maternal reactions to sleep behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, most parents believe that co-sleeping means security and the intimacy of a happy family, and so is essential to, and more natural for, a child's long-term emotional development. Some long-term follow-up studies comparing infants who slept with their parents with those who slept alone have shown that the children who co-slept were happier, less anxious, had higher self-esteem, were less likely to be afraid of sleep, had fewer behavioral problems, tended to be more comfortable with intimacy, and were generally more independent as adults (Crawford 1994;Keller and Goldberg 2004). Furthermore, when the young mother needs to return to work, bed-sharing provides the opportunity for mothers and infants to spend prolonged periods in close physical contact (described as a benefit of bed-sharing by many working mothers).…”
Section: Social and Culture Environment Of Bed Sharing In Chinamentioning
confidence: 99%